Izkoriščanje zapuščine slovenske empirične sociologije za današnje namene v okviru sekundarne analize - Štebe, Janez (Družboslovne razprave, 1999)
This article reviews the possibilities of the secondary analysis and the contribution of the social science data archives. The basic task of a data archive is that of achieving the transparency of data, which helps with the secondary analysis. Appropriately arranged data archive holdings represents preserved experience of past approaches to the research problems in a form, easy to use for present researchers. The archive puts emphasis on the most important social science studies in a country that follows from a reach tradition of empirical social science research. Used appropriately the data from the past can improve our understanding of the present moment in a Slovene society.
Keywords: družboslovne vede; sociologija; sociology; družboslovno raziskovanje; analiza; arhivi